A multistage mycobacterium tuberculosis subunit vaccine LT70 including latency antigen Rv2626c induces long-term protection against tuberculosis. Issue 7 (2nd July 2016) - Liu, Xun; Peng, Jinxiu; Hu, Lina; Luo, Yanping; Niu, Hongxia; Bai, Chunxiang; Wang, Qian; Li, Fei; Yu, Hongjuan; Wang, Bingxiang; Chen, Huiyu; Guo, Ming; et al.
ABSTRACT: To develop an effective subunit vaccine which could target tubercle bacilli with different metabolic states and provide effective protective immunity, we fused antigens ESAT6, Ag85B, peptide 190–198 of MPT64, and Mtb8.4 mainly expressed by proliferating bacteria and latency-associated antigen Rv2626c together to construct a multistage protein ESAT6-Ag85B-MPT64(190–198) -Mtb8.4-Rv2626c (LT70 for short) with the molecular weight of 70 kDa. The human T-cell responses to LT70 and other antigens were analyzed. The immune responses of LT70 in the adjuvant of DDA and Poly I:C and its protective efficacy against Mycobacterium tuberculosis ( M. tuberculosis ) infection in C57BL/6 mice were evaluated. The results showed that LT70 was stably produced in Escherichia coli and could be purified by successive salting-out and chromatography. LT70 could be strongly recognized by human T cells from TB patients and persons who are supposed latently infected with M. tuberculosis . The subunit vaccine LT70 generated strong antigen-specific humoral and cell-mediated immunity, and induced higher protective efficacy (5.41±0.37 Log10 CFU in lung) than traditional vaccine Bacillus Calmette-Guerin (6.01±0.33 Log10 CFU) and PBS control (6.53±0.26 Log10 CFU) at 30 weeks post vaccination (10 weeks post-challenge) against M. tuberculosis infection ( p < 0.05). These findings suggested that LT70 would be a promising subunit vaccine candidate against M. tuberculosis infection.